The role of human resource management in improving the welfare of farmers in ngada district - Wuli, Rofinus Neto (Jurnal Ekonomi, 2024)
Ngada Regency is one of East Nusa Tenggara Province's regencies with great agricultural potential. However, the welfare of farmers in this district is still relatively low. One of the factors causing this is the low quality of farmers' human resources (HR), so a planned role of human resources is needed to realize farmers' welfare. Thus, this research analyzes Human Resource Management's role in improving farmers' welfare in Ngada Regency. This research used qualitative research methods. Data collection techniques in this study were carried out by literature study, observation, and interviews. The data that has been collected is then analyzed using three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that implementing good HR management can improve the quality of farmers' human resources, increasing farmers' productivity and welfare. Here are some steps that can be taken to improve the quality of farmers' human resources, namely, farmer extension programs, farmer coaching programs, introduction and training programs for applying new technology, and social assistance programs for farmers. Agriculture can become the economy's driving force through implementing these programs and realizing optimal food security. Thus, welfare improvement and poverty reduction can be realized in Ngada Regency, East Nusa Tenggara Province.